2011
DOI: 10.1111/j.1467-839x.2011.01366.x
|View full text |Cite
|
Sign up to set email alerts
|

Extending self‐leadership research to the East: Measurement equivalence of the Chinese and English versions of the MSLQ

Abstract: In response to calls regarding the applicability of self‐leadership measurement in Eastern (collectivistic) and Western (individualistic) cultures, this study examined the psychometric properties and measurement invariance of the modified self‐leadership questionnaire (MSLQ). The sample consisted of 395 Chinese students and 241 Australian students. Results revealed that the modified self‐leadership questionnaire exhibited a satisfactory condition of psychometric properties across cultures. A series of multi‐sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…One of the most striking results of the present research was that the ASLQ, as an overall measure of self-leadership, is applicable to a nonWestern context, namely Turkish context. Early criticism of the self-leadership concept questioned the generalizability of the self-leadership construct to nonWestern cultures (e.g., Georgianna, 2007;Ho & Nesbit, 2009;Ho, Nesbit, Jepsen, & Demirian, 2012;Neubert & Wu, 2006). However, previous studies have found empirical evidence for the validity of the self-leadership construct across cultures, as measured with the RSLQ (e.g., Houghton et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…One of the most striking results of the present research was that the ASLQ, as an overall measure of self-leadership, is applicable to a nonWestern context, namely Turkish context. Early criticism of the self-leadership concept questioned the generalizability of the self-leadership construct to nonWestern cultures (e.g., Georgianna, 2007;Ho & Nesbit, 2009;Ho, Nesbit, Jepsen, & Demirian, 2012;Neubert & Wu, 2006). However, previous studies have found empirical evidence for the validity of the self-leadership construct across cultures, as measured with the RSLQ (e.g., Houghton et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Self-leadership was measured using the modified Selfleadership Questionnaire (MSLQ) developed by Ho and Nesbit [12]. Ho, Nesbit, Jepsen and Demirian [13] have provided evidence that the MSLQ is equivalent across the Chinese and Western cultures. Thus, the MLSQ is a reliable measure for this study to make valid cross-cultural comparisons.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, the MLSQ is a reliable measure for this study to make valid cross-cultural comparisons. For detailed discussion regarding the statistical procedures of testing measurement invariance, please refer to the study conducted by Ho, Nesbit, Jepsen and Demirian [13]. The MSLQ consists of 38 items describing various behaviors associated with self-leadership and participants use a 5-point Likert-type scale (1 = not all accurate; 2 = a little accurate; 3 = somewhat accurate; 4 = mostly accurate; 5 = completely accurate) to indicate how accurately each behavior describes them.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For some research, college students would make a reasonable sample, and if one is not interested in their current work experiences, they do not have to be employed. For example, Ho et al (2012) compared samples of Australian and Chinese college students regarding the self-leadership strategies that they used to self-regulate their own performance. The use of students controlled for many contextual factors that may affect self-management across occupations or life stages.…”
Section: Sample Comparability Across Countries or Culturesmentioning
confidence: 99%